Raman Monte Carlo simulation for light propagation in tissue with embedded object - Humaira Jaafar (2017)
Monte Carlo (MC) stimulation is one of the prominent simulation technique and is rapidly becoming the model of choice to study light-tissue interaction. Monte Carlo simulation for light transport in multi-layered tissue (MCML) is adapted and modelled with different geometry by integrating embedded objects of various shapes (i.e. sphere, cylinder, cuboid and ellipsoid) into the multi-layered structure. These geometries would be useful in providing a realistic tissue structure such as modelling for tumors, lymph nodes, head, blood vessels and other human body parts. In this context, the project deals with several MC simulations performed on various geometric medium and optical properties of a tissue. Stimulation of MCML with embedded object (MCML-EO) was improvised in which propagation of the photon in the defined medium was able to handle Raman scattering. Simulations were experimented on a modeled breast tissue with tumor by initializing tissue’s optical properties and were subjected to varying inputs of number of photons and probability. Simulation results records information such as diffused reflectance, diffused transmittance and absorbance. Moreover, results were presented in both A-line and B-line scans for embedded objects in order to determine spatial location where Raman photons were generated and predictions about the effect of tissue geometry.